Late information pick-up is preferred in basketball jump shooting - Ferraz de Oliveira, R.; Oudejans, R. R. D.; Beek, P. J. (Journal of Sports Sciences, 2006)
In this study we examined the timing of optical information pick-up in basketball jump shooting using an intermittent viewing technique. We expected shooters to prefer to look at the basket as late as possible under the shooting style used. Seven experts with a high shooting style and five experts with a low shooting style took 50 jump shots while wearing liquid-crystal glasses that opened and closed at pre-set intervals. In principle, under this constraint, the participants could control when they saw the basket by actively modulating the timing of their movements. Analyses of the phasing of the movements relative to the events defined on the glasses revealed that low-style shooters preferred to see the basket just before the ball passed their line of sight, whereas high-style shooters tended to view the basket from underneath the ball after it passed their line of sight. Thus, most shooters preferred to pick up optical information as late as possible given the adopted shooting style. We conclude that, in dynamic far aiming tasks such as basketball jump shooting, late pick-up of optical information is critical for the successful guidance of movements.